An alternative approach for quasi-truth - Coniglio, Marcelo Esteban; Cruz Silvestrini, Luiz Henrique da [UNESP] (Oxford University Press, 2014)
In 1986, Mikenberg et al. introduced the semantic notion of quasi-truth defined by means of partial structures. In such structures, the predicates are seen as triples of pairwise disjoint sets: the set of tuples which satisfies, does not satisfy and can satisfy or not the predicate, respectively. The syntactical counterpart of the logic of partial truth is a rather complicated first-order modal logic. In the present article, the notion of predicates as triples is recursively extended, in a natural way, to any complex formula of the first-order object language. From this, a new definition of quasi-truth is obtained. The proof-theoretic counterpart of the new semantics is a first-order paraconsistent logic whose propositional base is a 3-valued logic belonging to hierarchy of paraconsistent logics known as Logics of Formal Inconsistency, which was proposed by Carnielli and Marcos in 2002.
Keywords: Quasi-truth; logics of formal inconsistency; 3-valued paraconsistent logic; first-order paraconsistent logic; 3-valued model logic; paraconsistent model theory